An Extracellular Polysaccharide-Rich Organic Layer Contributes to Organization of the Coccosphere in Coccolithophores - Walker, Charlotte E.; Heath, Sarah; Salmon, Deborah L.; Smirnoff, Nicholas; Langer, Gerald; Taylor, Alison R.; Brownlee, Colin; Wheeler, Glen L. (Frontiers in Marine Science, 2018)
Coccolithophores are globally abundant marine microalgae characterised by their ability to form calcite platelets (coccoliths). The coccoliths are produced internally in a Golgi-derived vesicle. Mature coccoliths are extruded from the cell to form a protective covering on the cell surface, known as the coccosphere. Current evidence indicates that calcite precipitation in the coccolith vesicle is modulated by coccolith-associated polysaccharides (CAPs). Whilst previous research into CAPs has focussed on their roles in calcite precipitation within the coccolith vesicle, little is known of their extracellular roles. Using fluorescent lectins, we visualise the extracellular polysaccharide-rich organic layer associated with external coccoliths and demonstrate that it differs between species in structure and composition. Biochemical analysis of polysaccharide extracted from coccoliths indicated substantial differences between species in monosaccharide composition and uronic acid content. In Coccolithus braarudii our studies indicate that polysaccharide-rich material is extruded with the coccoliths, where it plays a role in the adhesion of the coccoliths to the cell surface and contributes to the overall organisation of the coccosphere. Together, these results highlight the important extracellular roles of CAPs and their contribution to the dynamic nature of the coccosphere.